DEPICTING THE IMAGE OF A BEAR IN SIMILAR POSITIONS IN THE WORKS OF EUROPEAN AND ASIAN ANIMALISTS - Choriyeva Asila (American Journals Publishing, 2023)
In the article, the use of the image of a bear in the same plot in the literary genre in the works of the European, Canadian writer Ernest Seton Thompson and the Uzbek writer from the Asian region, Normurod Norqobilov, is presented with reasonable arguments. The feelings and experiences of the bear are described as similar to those of people, and it is no exaggeration to say that these two works created by the writers can be a great motivation to understand the creatures of the wild world and arouse compassion in people.
Keywords: devaluation of ethical-emotional factors, disconnection of personal relationships, the protection of the environment.